Deskripsi Kebutuhan Media Pembelajaran Komik Berbasis Kontekstual Pada Materi Torsi di SMA - Aulia, Maryam; Normilawati, Normilawati; Yuliani, Hadma; Azizah, Nadia (COMPTON: Jurnal Ilmiah Pendidikan Fisika, 2021)
Abstract The teacher's attention in choosing the learning media used is an important discussion. Therefore, an analysis of students' needs for learning media was carried out. The aims of this study were to 1) find out the learning media used by teachers during the learning process; 2) get the difficulties faced by students in learning physics; 3) suggesting learning media that need to be developed on the torsion concept material in high school. The data analysis technique used is descriptive quantitative analysis technique. This study uses a Research and Development (R&D) research approach with reference to a 3-D model (define, design, develop). This research is an initial research so that only the refine stage is carried out. The results of this study are 1) the learning media used by teachers are very diverse, in this case as many as 18% use learning videos, 18% use videos from YouTube, 18% use PPT, 8% use modules, 14% use worksheets, 16% use handbook and 8% use of educational websites; 2) as many as 84.21% of students feel that they have obstacles in learning physics due to the complexity of the material that contains formulas that make students quickly forget to remember the teacher's explanations and how to answer questions and the lack of direct practice so that it requires extra understanding; 3) as many as 94.74% of students stated the need for contextual-based comics as a medium of learning.